Tunable electronic properties of arsenene/GaS van der Waals heterostructures. Issue 45 (1st June 2017) - Li, Xiao-Hua; Wang, Bao-Ji; Cai, Xiao-Lin; Zhang, Li-Wei; Wang, Guo-Dong; Ke, San-Huang
Abstract : On the basis of density functional electronic calculations, we identify that the arsenene/GaS heterostructure is a promising photocatalyst for water splitting and find that its electronic properties can be continuously tuned by external strain. Abstract : Finding novel atomically thin heterostructures and understanding their electronic properties is critical for developing better nanoscale electronic and optoelectronic devices. In this work, we investigate the structural and electronic properties of arsenene/GaS van der Waals (vdW) heterostructures using first-principles calculations. Our results suggest that this heterostructure has an intrinsic type-II band alignment and an indirect band gap. Comparing the calculated band edge positions to the redox potentials of water, we identify that the arsenene/GaS vdW heterostructure is a promising photocatalyst for water splitting. Moreover, we also find that intriguing indirect–direct and semiconductor–metal transitions can be induced by strain. In particular, under certain strain, degenerate valleys of conduction band bottoms will be created, which suggests potential applications in valleytronics.